2002
DOI: 10.1002/env.539
|View full text |Cite
|
Sign up to set email alerts
|

Meshing noise effect in design of experiments using computer experiments

Abstract: International audienceThis work is intended to show the influence of grid length and meshing technique on the empirical modeling of current distribution in an industrial electroplating reactor. This study confirms the interest of usual DOEs for computer experiments. Any 2D mesh generator induced, in this sensitive case, a significant noise representing only less than 5 per cent of the response. The ‘experimental error’ obeys a normal distribution and the associated replicate SDs represents 20 per cent of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Caire et al [21] showed that the secondary distribution of potential is particularly sensitive to the grid length. This effect is due to the post-processing from the unknown factor potential V of current density J which mainly contributes to coupling in terms of mass and heat transfers (see Eq.…”
Section: Coupling Aspects and Meshing Boundsmentioning
confidence: 99%
“…Caire et al [21] showed that the secondary distribution of potential is particularly sensitive to the grid length. This effect is due to the post-processing from the unknown factor potential V of current density J which mainly contributes to coupling in terms of mass and heat transfers (see Eq.…”
Section: Coupling Aspects and Meshing Boundsmentioning
confidence: 99%
“…Double precision is required since current density is post-processed from the potential distribution and careful meshing is necessary as shown by Caire and Chifflet [12].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…They appear in various fields of electrochemical engineering such as electrodeposition [1,4,5,7,[10][11][12][13][14][15][16], electro-machining [17], electropolishing [8], and corrosion processes [6]. Most popular commercial codes are now able to compute primary, secondary or tertiary current distributions for any geometry.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many authors tried to compute moving profiles by use of different numerical methods such as finite difference method (FDM) [6,10,12,14], boundary element method (BEM) [1,5,9], finite element method (FEM) [7,11,12], or specific methods [16]. All these authors used the same manual iterative process but Chauvy and Landolt [17] who developed a specific FORTRAN 77 code to compute the shape evolution of cavities produced by multistep electrochemical micromachining (the CREVICER code [18] developed for corrosion purposes does not have yet this capability).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation